(3ebOeI aJM GdQMef HJaSjQ GdaQbGfs - (3YHO GdQMef Hf eMeO Hf YHO GdQMef GdYeQj GdYdjej , CHh Gdjef , J (B928 (3g`s
(3ChdgG (B:s
(3hHYO adeG ef Gddg SHMGfg HEceGd cJGH aJM GdQMef s
(3BNQgG (B:s
(3Mce TGgO GdRhQ ai ShQI GdML TgGOI GdGYei ai ShQI GdCMRGH s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B(9287) s
Keywords: (3CUhd Gdabgs